2017
DOI: 10.1016/j.clon.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conformal Craniospinal Radiotherapy Techniques Can Underdose the Cranial Clinical Target Volume if Leptomeningeal Extension through Skull Base Exit Foramina is not Contoured

Abstract: AimsCraniospinal irradiation (CSI) remains a crucial treatment for patients with medulloblastoma. There is uncertainty about how to manage meningeal surfaces and cerebrospinal fluid (CSF) that follows cranial nerves exiting skull base foramina. The purpose of this study was to assess plan quality and dose coverage of posterior cranial fossa foramina with both photon and proton therapy.Materials and methodsWe analysed the radiotherapy plans of seven patients treated with CSI for medulloblastoma and primitive ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…However, it should be mentioned that knowledge on the uncertainties related to possible motion of the target and correct target volume delineation are pre-requisites for highly-conformal techniques. The latter becomes relevant at the meningeal surfaces and cerebrospinal fluid in the dural reflections of the cranial nerves [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be mentioned that knowledge on the uncertainties related to possible motion of the target and correct target volume delineation are pre-requisites for highly-conformal techniques. The latter becomes relevant at the meningeal surfaces and cerebrospinal fluid in the dural reflections of the cranial nerves [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the advantages of HT, over 3D-CRT or IMRT, as it allows to irradiate the entire neuroaxis in one single volume [22] , and delivers homogeneous radiation, thus avoiding over- or under-dosing [23] , [24] . HT has better target volume dose distribution and homogeneity compared to conventional or intensity-modulated techniques [25] , [26] , and also reduces the dose delivered to OAR [27] , [28] .…”
Section: Discussionmentioning
confidence: 87%
“…During optimisation, attempts to reduce the dose to the lenses were carried out with caution to prevent underdosing the cribriform plate, which can cause relapse [14]. An additional optimisation structure, which included the PTV around the cribriform plate and optic nerves, was used to ensure coverage in this high-risk area (Supplementary Figure S1).…”
Section: Treatment Plan Optimisationmentioning
confidence: 99%